Formation of an innovative model of the Hungarian business economy - Nagy, Szabolcs; Pererva, P. G. (My University, 2021)
It is proved that the innovative development of Hungary as a country with an economy in transition, largely dependent on the economic policy of the European Union as a whole, largely depends on economic cooperation in the field of innovation with other countries. And first of all, in our opinion, attention should be paid to the effectiveness of innovative business cooperation with the closest neighbor - Ukraine.
Формирование инновационной модели бизнес-экономики Венгрии
Keywords: innovative development; economic cooperation; efficiency; Hungary; Ukraine